ANALISIS KEBIJAKAN DERADIKALISASI DI LEMBAGA PEMASYARAKATAN TERHADAP PELAKU TINDAK PIDANA TERORISME DI INDONESIA - Saputra, Yayan; Jayakusuma, Zulfikar; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The criminal act of terrorism is a crime against humanity that results in damage to infrastructure, the emergence of anxiety in the community and increasing suspicion among religious communities. Many observers say the emergence of terrorism stems from radicalism. Radicalism is an attitude that craves total change and is revolutionary by reversing drastic values through extreme violence and actions. To eradicate criminal acts of terrorism, Indonesia uses two methods, namely a harsh approach through Detachment 88 as the executor. And the only soft approach through BNPT as the implementer. The soft approach used by the BNPT is counter radicals and deradicalisation. Deradicalization is changing the ideology of a person who was previously radical to no longer radical. This de-radicalization is done inside the prison and outside the prison.This type of research is classified in the type of normative legal research, namely research on the effective law that is currently in effect, the nature of this research is descriptive, that is to describe systematically, the facts and characteristics of the object being studied appropriately. Sources of data used are primary and secondary data, data collection techniques used are through library research sourced from legislation, books, official documents, publications, and research results.Based on the results of the study there are main problems that can be concluded that first, the lack of knowledge of prison officers in dealing with terrorist prisoners. Second, not all terrorist inmates want to join the deradicalization program. Third, mixing terrorist inmates with other criminal convicts in one prison. And fourth, there are people who do not want to accept ex-convicts and their families back in their midst. Suggestion writer, the BNPT should provide training and knowledge to prison officers in dealing with terrorist prisoners, prison officers or the BNPT must find a solution so that every terrorist prisoner wants to participate in the de-radicalization program, place terrorist prisoners in prison that only contain terrorist prisoners and educate the public about implementation of the de-radicalization program in prison so that there is no negative stigmatization of former terrorist inmates who return to the society.Keywords: Criminal Acts of Terrorism, Radicalism, Deradicalization